Neuronavigation-assisted percutaneous balloon compression for the treatment of trigeminal neuralgia: The technique and short-term clinical results. (4th July 2015) - Aydoseli, Aydin; Akcakaya, Mehmet Osman; Aras, Yavuz; Sabanci, Pulat Akin; Unal, Tugrul Cem; Sencer, Altay; Hepgul, Kemal; Unal, Omer Faruk; Barlas, Orhan; Izgi, Nail
Abstract: Background . Percutaneous balloon compression (PBC) has been widely used in the treatment of trigeminal neuralgia. However, this technique has a steep learning curve and significant complications were reported that were related to foramen ovale puncturing. The aim of this study was to evaluate the clinical results of a small patient group who underwent neuronavigation-assisted PBC. Methods . An intraoperative computed tomography (CT) device (CereTom, Neurologica, Danvers, MA/USA) was used to obtain CT scans with 2-mm slice thicknesses. The data were transferred to a neuronavigation system planning station (BrainLab, Feldkirchen, Germany). A soft touch registration system was used for image registration. With the image guidance, a trajectory was defined and the foramen ovale was cannulated using neuronavigation and Hartel's landmarks. Results . Sixteen procedures were performed on 13 patients (4 female and 9 male) without complications. The total length of the procedure was not more than 57 min in all instances. Conclusions . We believe that image-guided neuronavigation is useful for neurosurgeons who are at the beginning of their PBC learning curve. It may also be an alternative for particular patients with significant anatomic variations that result in an unsuccessful foramen ovale puncture.